Business process reengineering : an ICT approach - Susanto, Heru, 1977-; Fang-Yie, Leu; Chen, Chin Kang (Oakville, ON ; New Jersey : Apple Academic Press, 2019)
"This volume, Business Process Reengineering: An ICT Approach, shows how ICT (information and communications technology) can play the role of a driver of business process reengineering (BPR). ICT can aid in enabling improvement in BPR activity cycles as it provides many components that enhance performance that can lead to competitive advantages. IT can interface with BPR to can help to improve main business processes in terms of communication, inventory management, data management, management information systems, customer relationship management (CRM), computer-aided design (CAD), computer-aided manufacturing (CAM), and computer-aided engineering (CAE). This volume explores these issues in depth. BPR is perhaps best described as the restructuring of an organization or enterprise to change the way of business process designs and to implement new workflows and day-to-day processes. Business process reengineering, at times, is often perceived as similar to business process redesign. In fact, these two differ in the sense that business process reengineering involves taking down the whole structure of the workflow process and starting over from scratch; on the other hand, business process redesign takes a more conservative approach that may leave some of the present structure and may merely tweak certain processes in isolation"--
The success of information technology : the greatest -- Empowering agent of business process reengineering -- Heading toward a new direction of development through -- ICT emerging technology -- Information technology-enabled business process reengineering : organizational and human resource dimensions -- Rethinking, replanning, and rebuilding : customer expectations -- ICT as a driver of business process reengineering -- Corporate goals and creating value : improving organizational -- Innovation -- Reengineering processes : key toward information technology -- Improvements -- Crafting possibility improvement : an information system -- Approach -- Process restructuring: customers, suppliers, and business -- Partner dimensions -- Application of six sigma in information technology : a business -- Process redesign perspective -- Managing the role of information technology : alteration of -- Corporate changes -- The role of information technology : a driving force behind -- The productivity of organizations -- Business process reengineering : producing a higher level of -- Output to a specific product in a specific time -- Technology enhancement redesign business structure : -- From functional to cross-functional.
OCLC-licensed vendor bibliographic record.
Keywords: Reengineering (Management); Information technology -- Management; Telecommunication -- Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Information Management